pengaruh luas lahan, teknologi dan pelatihan terhadap pendapatan petani padi dengan produktivitas sebagai variabel intervening di kecamatan mengwi - arimbawa, putu dika; Widanta, A.A. Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This research have a main purpose to identify the impact of landsize, technology and training to paddy farme’s income with productivity as an intervening variable in Mengwi. The data is obtained by doing observation, interview, and depth interview. The technique that used for sampling is proporsionate random sampling. The amount of sample is 99 respondent. This research using path analysis to analyze direct relation between one to other variables and sobel analysis is to analyze undirect relation with intervening variable. Depend on this research we know that land size, technology, and training have positive and significant impact to farmer’s income in Mengwi. Productivity variable as an intervening variable which have undirect impact with land size, technology, and training to paddy farmer’s income in Mengwi. Keywords : land size, technology, training, income and productivity